Arthroscopic partial medial meniscectomy - Dašić Žarko; Radoičić Dragan (Vojnosanitetski Pregled)
Background/Aim. Meniscal injuries are common in professional or recreational sports as well as in daily activities. If meniscal lesions lead to physical impairment they usually require surgical treatment. Arthroscopic treatment of meniscal injuries is one of the most often performed orthopedic operative procedures. Methods. The study analyzed the results of arthroscopic partial medial meniscectomy in 213 patients in a 24-month period, from 2006, to 2008. Results. In our series of arthroscopically treated medial meniscus tears we noted 78 (36.62%) vertical complete bucket handle lesions, 19 (8.92%) vertical incomplete lesions, 18 (8.45%) longitudinal tears, 35 (16.43%) oblique tears, 18 (8.45%) complex degenerative lesions, 17 (7.98%) radial lesions and 28 (13.14%) horisontal lesions. Mean preoperative International Knee Documentation Committee (IKDC) score was 49.81%, 1 month after the arthroscopic partial medial meniscectomy the mean IKDC score was 84.08%, and 6 months after mean IKDC score was 90.36%. Six months after the procedure 197 (92.49%) of patients had good or excellent subjective postoperative clinical outcomes, while 14 (6.57%) patients subjectively did not notice a significant improvement after the intervention, and 2 (0.93%) patients had no subjective improvement after the partial medial meniscectomy at all. Conclusion. Arthroscopic partial medial meniscetomy is minimally invasive diagnostic and therapeutic procedure and in well selected cases is a method of choice for treatment of medial meniscus injuries when repair techniques are not a viable option. It has small rate of complications, low morbidity and fast rehabilitation.